2016
DOI: 10.1177/0022466916632495
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Diversity of Participants in Research Supporting Evidence-Based Practices for Learners With Autism Spectrum Disorder

Abstract: Selection of a special education evidence-based practice (EBP) requires developing an understanding of what interventions work as well as for whom they are effective. This review examined participant characteristics in the EBP literature for learners with autism spectrum disorders (ASD) identified by the National Professional Development Center on Autism Spectrum Disorders. Results indicated very limited representation of diverse participants in the entire body of research, and when reported, White youth repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
106
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 31 publications
6
106
1
Order By: Relevance
“…Underreporting of cultural factors in the field of ASD is, however, well documented (Broder-Fingert et al 2017;Kistner and Robbins 1986;National Autism Center 2015;Pierce et al 2014;West et al 2016;Wong et al , 2015. For instance, Pierce et al (2014) evaluated methodological practices for reporting ethnicity for study participants in ASD studies published in three autism-related academic journals.…”
Section: The Gap-reach Checklist To Assess Reporting Of Cultural Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Underreporting of cultural factors in the field of ASD is, however, well documented (Broder-Fingert et al 2017;Kistner and Robbins 1986;National Autism Center 2015;Pierce et al 2014;West et al 2016;Wong et al , 2015. For instance, Pierce et al (2014) evaluated methodological practices for reporting ethnicity for study participants in ASD studies published in three autism-related academic journals.…”
Section: The Gap-reach Checklist To Assess Reporting Of Cultural Factorsmentioning
confidence: 99%
“…The reviews of intervention research reporting on evidence-based practices (EBPs) for children and youth with ASD (National Autism Center 2015; Wong et al , 2015 also showed that most efficacy studies did not systematically include information on cultural demographics of their participants. More specifically, these studies did not describe ethnicity, nationality, or race of the participants other than White, Caucasian, or European-American (West et al 2016). Inadequate reporting of cultural factors presents a number of methodological issues affecting both research and practice.…”
Section: The Gap-reach Checklist To Assess Reporting Of Cultural Factorsmentioning
confidence: 99%
See 3 more Smart Citations